Acid etching additive, phosphoric acid etching agent and preparation method and application thereof
By introducing permeable, hydrophilic and polymerizable etching additives into the etching agent, the problem of unstable bonding on the dentin surface is solved, and a more stable bonding effect and higher bonding strength are achieved.
Patent Information
- Application Number
- CN202510964366.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-09-09
AI Technical Summary
After the dentin surface is pretreated with acid etching agents, the bonding effect between the bonding material and the dentin is unstable, which can easily lead to clinical operation errors.
An acid etching additive is used, which has permeability, hydrophilicity, low volatility and polymerizability. It can penetrate into the dentin collagen fiber network, be miscible with the water in the dentin collagen fiber network, and be retained during the drying process to maintain the upright fluffy structure of the collagen fibers. At the same time, it forms chemical bonds with the bonding material to enhance the bonding effect.
By using acid etching additives, the upright and fluffy state of the collagen fiber network is stably maintained, the bonding effect between the bonding material and dentin is enhanced, and the stability and bonding strength of clinical operations are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dental materials, and in particular relates to an acid etching additive, a phosphoric acid etching agent, and a preparation method and application thereof. Background Art
[0002] Teeth primarily consist of four parts: enamel, dentin, pulp, and cementum. Enamel is primarily composed of approximately 97% by mass of inorganic minerals (primarily hydroxyapatite), 2% water, and 1% trace organic matter. Structurally, enamel consists of enamel prisms and interprisms. In the oral cavity, the enamel surface is typically nonpolar and has low surface energy, making it less conducive to bonding. Dentin is primarily composed of approximately 70% by mass of inorganic minerals (primarily hydroxyapatite), 18% protein, 10% water, and 1.5% trace organic matter. Structurally, dentin consists of tubules, processes of odontoblasts within the tubules, and peritubular and intertubular dentin. During tooth preparation, the high-speed cutting and compression of the bur easily forms a 1–8 μm thick smear layer on the dentin surface, which is detrimental to dentin bonding.
[0003] Etching agents are important materials used in oral care, primarily for etching tooth surfaces. Their primary functions include removing plaque from tooth surfaces, enhancing the adhesion between teeth and restorative materials, and improving restoration effectiveness. Etching agents are primarily composed of acidic solutions, typically in the form of liquid or gel-like pastes. These etchants remove tartar and plaque from tooth surfaces through the action of acidic solutions, achieving a cleaning effect. Furthermore, etchants can remove the smear layer, increasing the diameter of the dentinal tubule openings and exposing the collagen fiber network, thereby providing the necessary micro-retention surface for subsequent restoration work.
[0004] Chinese patent CN 111467248 A discloses a phosphoric acid etchant and its preparation method. The phosphoric acid etchant is made from phosphoric acid, fumed silica, glycerol, sodium lauryl ether sulfate, polyethylene glycol, methylene blue, and purified water. The weight proportions are 350-380 parts phosphoric acid, 100-250 parts fumed silica, 100-250 parts glycerol, 10-50 parts sodium lauryl ether sulfate, 20-50 parts polyethylene glycol, 0.01-1 part methylene blue, and 250-400 parts purified water. The phosphoric acid etchant has the advantages of being a non-flowing colloid that can be placed in a pre-coating position. Stirring the phosphoric acid etchant during use reduces its viscosity for even coating. Stirring the colloid after use also reduces its viscosity, facilitating rinsing and leaving no residue. In clinical use, the material has an appropriate viscosity and a blue color that makes it easily recognizable on tooth enamel surfaces, making it easier to use.
[0005] Currently, after the dentin surface is pre-treated with acid etching agents, the bonding effect between the bonding material and the dentin is unstable, which can easily lead to clinical operation errors. Summary of the Invention
[0006] The purpose of the present invention is to provide an acid etching additive to solve the technical problem that after the acid etching pretreatment of the dentin surface by the acid etching agent, the bonding effect between the adhesive material and the dentin is unstable, which is easy to cause clinical operation errors.
[0007] To achieve the above object, the present invention adopts the following technical solutions: An acid etching additive can penetrate into the dentin collagen fiber network during the acid etching process, be miscible with the water in the dentin collagen fiber network, and be retained in the dentin collagen fiber network during the drying process to maintain the upright fluffy structure of the collagen fibers.
[0008] The acid etching additive of the present invention has certain permeability, hydrophilicity, low volatility and polymerizability. Among them, the permeability enables the acid etching additive to penetrate into the dentin collagen fiber network; the hydrophilicity enables the acid etching additive to be miscible with water and form uniform support for the collagen fibers through hydrogen bonding, maintaining the upright fluffy structure of the collagen fibers; the low volatility prevents the acid etching additive from being lost as the dentin surface is blown dry, thereby ensuring the water retention and support effect; the polymerizability enables the acid etching additive to form a chemical bond with the bonding material, thereby enhancing the bonding effect.
[0009] Preferably, the etching additive comprises at least one of hydroxyethyl methacrylate, N-acryloylmorpholine, and 2-hydroxyethyl acrylate. Each of hydroxyethyl methacrylate, N-acryloylmorpholine, and 2-hydroxyethyl acrylate possesses certain permeability, hydrophilicity, low volatility, and polymerizability. These additives are capable of penetrating the dentin collagen fiber network during the etching process, becoming miscible with the water in the dentin collagen fiber network, and remaining in the dentin collagen fiber network during the drying process, thereby maintaining the upright, fluffy structure of the collagen fibers.
[0010] Preferably, the acid etching additive includes at least one of hydroxyethyl methacrylate and 2-hydroxyethyl acrylate. Both hydroxyethyl methacrylate and 2-hydroxyethyl acrylate are hydrophilic due to the hydroxyethyl group, which allows for strong hydrogen bonding with collagen fibers. Furthermore, their small molecular size and good permeability allow them to better penetrate the dentin collagen fiber network and provide a more uniform and solid support.
[0011] Preferably, the acid etching additive includes hydroxyethyl methacrylate. Hydroxyethyl methacrylate has a high homopolymer elastic modulus and strong anti-collapse ability. It also has low volatility and, under the same drying conditions, retains sufficient amount, thereby providing sufficient collagen support.
[0012] The second object of the present invention is to provide a phosphoric acid etchant for dentin bonding pretreatment, wherein the phosphoric acid etchant comprises, by weight percentage of the total weight, 34-38% phosphoric acid, 1-5% etching additive, and 25-43% purified water. Phosphoric acid, as the main functional component of the phosphoric acid etchant, can dissociate into hydrogen ions and has an etching effect. Through the etching effect, tartar and plaque on the tooth surface can be removed, thereby achieving a cleaning effect. In addition, the etching effect can also remove the smear layer, increase the diameter of the dentinal tubule opening, and expose the collagen fiber network, thereby providing the necessary micro-retention surface for subsequent repair work. Phosphoric acid can control the demineralization depth, leaving no residue after rinsing, and does not affect the penetration of the etching additive. The core function of purified water is to promote the ionization of phosphoric acid to release hydrogen ions, forming a stable acidic environment.
[0013] Preferably, the phosphoric acid etchant also includes 3-10% of a thickener. Because phosphoric acid solution itself is a low-viscosity liquid with high fluidity, it can easily flow to non-target areas when applied directly, and it can't stay on vertical tooth surfaces and sag. Adding a thickener can confine the strong acid to the target area, preventing accidental damage to other areas, ensuring sufficient contact time between the etchant and the tooth surface, and providing ideal thixotropy, making the phosphoric acid etchant easy to apply and non-sag.
[0014] Preferably, the thickener comprises at least one of silicon dioxide and xanthan gum.
[0015] Preferably, silica is added as a thickener. This silica is either fumed or colloidal. Its silicon-oxygen bonds are extremely stable in strong acids, resisting hydrolysis, degradation, or structural breakdown, maintaining a very stable viscosity. Fumed silica forms a three-dimensional network structure through hydrogen bonding between its particles. This network is easily disrupted by shear forces (e.g., stirring or spreading), reducing the viscosity (thinning the system) and facilitating handling. Once the shear force is removed, the network quickly recovers, increasing the viscosity (thickening), and maintaining a secure hold on vertical tooth surfaces, preventing sagging. Furthermore, due to its chemical inertness, silica does not interfere with the phosphoric acid reaction. The thixotropic gel it forms ensures uniform coverage of the etchant, allowing for highly controllable etching depth and morphology, while minimizing air bubbles and reducing uneven etching. After etching, the surface leaves minimal residue and is easily rinsed, leaving the collagen fiber network fully exposed and fluffy, providing an ideal bonding base for the adhesive.
[0016] Preferably, the phosphoric acid etching agent further comprises 0.01-0.1% of a developer.
[0017] Preferably, the color developer comprises at least one of cobalt blue, methylene blue, and brilliant blue. The color developer primarily develops color, facilitating the determination of clean rinsing of the acid etchant. Since thickeners and color developers are typically insoluble in the strongly acidic phosphoric acid, the cosolvent provides a compatible environment, helping them disperse or dissolve evenly in the phosphoric acid system, forming a stable, uniform gel or viscous liquid. Furthermore, the cosolvent's surface contains abundant hydroxyl groups, which work together with silica to thicken the etchant.
[0018] Preferably, the phosphoric acid etching agent further comprises 15-30% of a solvent.
[0019] Preferably, the cosolvent includes at least one of polyethylene glycol and glycerol.
[0020] Preferably, polyethylene glycol is added as a cosolvent. Polyethylene glycol itself has a significant thickening effect. Its molecular structure and chain length can more effectively "entwine" or support with commonly used thickeners to form a more stable and thixotropic gel structure, thereby improving physical stability.
[0021] The third object of the present invention is to provide a method for preparing the phosphoric acid etchant, comprising the steps of: mixing all raw materials and stirring them uniformly to obtain the phosphoric acid etchant. The raw materials are directly stirred and mixed at room temperature and pressure, which is simple and easy to perform.
[0022] Preferably, the stirring speed is 500-1500 rpm and the stirring time is 1-5 hours. High-speed stirring can improve the dispersion efficiency and homogeneity of the raw materials, thereby improving the quality and performance of the phosphoric acid etching agent.
[0023] A fourth object of the present invention is to provide a method for applying the phosphoric acid etchant in dentin bonding pretreatment, comprising the following steps: S1. The phosphoric acid etchant is applied to the dentin surface for etching for 10-40 seconds; S2. Rinse the phosphoric acid etchant off the dentin surface with clean water and then blow dry until no visible liquid flow is observed. S3. Repair with adhesives and resins.
[0024] Through research, the present invention found that when the existing acid etchant is used to etch and rinse the dentin surface and then blow-dry the water, due to subjective errors in naked eye observation, the degree of drying is difficult to accurately control, and the water is easily blown too dry, causing the collagen fiber network to collapse, affecting the subsequent bonding effect.
[0025] Compared with the prior art, the present invention has the following beneficial effects: The acid etching additive of the present invention can penetrate into the dentin collagen fiber network during the acid etching process and be miscible with the moisture in the dentin collagen fiber network. In this way, the moisture in the dentin collagen fiber network is locked and retained, which is conducive to maintaining the collagen fiber network in an upright and fluffy state; moreover, the acid etching additive itself can form support for the collagen fibers through hydrogen bonding. After being miscible with moisture, the acid etching additive occupies the position where the original moisture was located, and the collagen fibers are full of the acid etching additive. Compared with the original moisture content, the acid etching additive can provide a more uniform and powerful support effect, further consolidating the upright and fluffy state of the collagen fiber network. The upright and fluffy state of the collagen fiber network and the polymerizable characteristics of the acid etching additive provide a more excellent bonding base for the subsequent bonding of the bonding material. The bonding effect will not be affected by the inadequate control of the degree of drying. The bonding between the bonding material and the dentin is firm and the effect is stable, thereby improving the clinical fault tolerance rate. DETAILED DESCRIPTION
[0026] The present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are intended to illustrate the present invention but are not intended to limit the scope of the present invention.
[0027] In the following examples / comparative examples of the present invention, all raw materials used are commercially available. Unless otherwise specified, all percentages in all examples / comparative examples are by weight and are based on the total weight.
[0028] The present invention provides an acid etching additive as follows: during the acid etching process, the acid etching additive can penetrate into the dentin collagen fiber network, become miscible with the water in the dentin collagen fiber network, and remain in the dentin collagen fiber network during the drying process to maintain the upright and fluffy structure of the collagen fibers; Specifically, the acid etching additive includes at least one of hydroxyethyl methacrylate, N-acryloylmorpholine, and 2-hydroxyethyl acrylate.
[0029] The present invention provides a phosphoric acid etching agent as follows: calculated by mass percentage of the total weight, comprising: 34-38% acidic body, 1-5% etching additive, 25-43% purified water, 3-10% thickener, 15-30% co-solvent and 0.01-0.1% color developer; Specifically, the thickener includes at least one of silicon dioxide and xanthan gum; The cosolvent comprises at least one of polyethylene glycol and glycerol; The color developer includes at least one of cobalt blue, methylene blue and brilliant blue.
[0030] The present invention provides a method for preparing a phosphoric acid etching agent, comprising the following steps: After mixing all the raw materials, stir at a speed of 500-1500 rpm for 1-5 hours to obtain the product.
[0031] The present invention provides a method for applying a phosphoric acid etchant in dentin bonding pretreatment, comprising the following steps: S1. The phosphoric acid etchant is applied to the dentin surface for etching for 10-40 seconds; S2. Rinse the phosphoric acid etchant off the dentin surface with clean water and then dry it until no visible liquid flow is observed. S3. Repair with adhesives and resins.
[0032] Example 1 In this example, referring to the raw material formula, preparation method and application method provided above, according to the raw material components and usage ratios shown in Table 1, different treatment groups were set with the specific composition of the etching additive as a variable to investigate the effect of this variable on the use effect of the phosphoric acid etching agent.
[0033] Table 1 (Unit: mass percentage / %)
[0034] Example 2 In this example, referring to the raw material formula, preparation method and application method provided above, according to the raw material components and usage ratios shown in Table 2, the specific composition of the thickener was used as a variable, and different treatment groups were set to investigate the effect of this variable on the use effect of the phosphoric acid etching agent.
[0035] Table 2 (Unit: mass percentage / %)
[0036] Example 3 In this example, referring to the raw material formula, preparation method and application method provided above, according to the raw material components and usage ratios shown in Table 3, the specific composition of the co-solvent was used as a variable, and different treatment groups were set to investigate the effect of this variable on the use effect of the phosphoric acid etchant.
[0037] Table 3 (Unit: mass percentage / %)
[0038] Example 4 Referring to the preparation method and application method provided above and the raw material components and dosage ratios in Table 1, 4-META (i.e., 4-methacryloyloxytrimellitic anhydride) was used as an etching additive to investigate the effect of 4-META on the use effect of phosphoric acid etching agent.
[0039] Example 5 With reference to the preparation method and application method provided above and the raw material components and dosage ratios in Table 1, glycerol was used as an etching additive to investigate the effect of glycerol on the use effect of phosphoric acid etching agent.
[0040] Comparative Example Referring to the preparation method, application method and the raw material components and dosage ratios provided above and in Table 1, the etching additive was removed and the amount of purified water was adjusted to 34.9% to investigate the effect of not adding the etching additive on the use effect of the phosphoric acid etchant.
[0041] Performance testing experiments 1. Determine the shear bond strength of each treated adhesive on the dentin surface. Shear bond strength testing was performed according to the standard YY / T 0518-2009, Polymer-Based Adhesives for Dental Restorations. Data were statistically analyzed using SPSS software. The adhesive used was 3M ESPE Single Bond Universal.
[0042] 2. The statistical and measurement results are shown in Table 4.
[0043] Table 4
[0044] From Table 4 we can see that: (1) The shear bonding strength of each treatment in Examples 1-3 was above 20 MPa, and under the raw material ratio of Treatment 1-1 in Example 1, the shear bonding strength reached 27.8 MPa.
[0045] (2) The measurement results of each treatment in Example 1 illustrate the importance of selecting the type of acid etching additive. When the acid etching additive is a single component, the effect of hydroxyethyl methacrylate is the most obvious. This is because, compared with the other two components, hydroxyethyl methacrylate has a higher homopolymer elastic modulus, strong anti-collapse ability, and low volatility. Under the same drying conditions, the retention amount is sufficient, thus being able to provide sufficient collagen support; while N-acryloylmorpholine has a weaker ability to bind to hydrogen bonds, a larger molecular volume, and lower permeability; 2-hydroxyethyl acrylate has a lower homopolymer elastic modulus, resulting in lower anti-collapse ability. When the acid etching additive is a combination of hydroxyethyl methacrylate and 2-hydroxyethyl acrylate and / or N-acryloylmorpholine, the shear bonding strength decreases to a certain extent compared with using hydroxyethyl methacrylate alone.
[0046] (3) The results of each treatment in Example 2 illustrate the importance of selecting the type of thickener. When the thickener is a single component, the effect of silica is more obvious. This is because, compared with xanthan gum, the chemical inertness of silica does not interfere with the phosphoric acid reaction. The thixotropic gel formed ensures uniform coverage of the acid etchant, the acid etching depth and morphology are highly controllable, bubbles are not easily generated, and uneven acid etching is reduced. There is very little surface residue after acid etching, which is easy to rinse. The collagen fiber network is fully exposed and the structure is fluffy, creating an ideal microporous structure for the penetration of the acid etching additive, and the bonding strength is high and stable. The hydrophilic organic matter remaining after the degradation of xanthan gum intensifies the hygroscopic expansion of the collagen fibers, making them more likely to collapse during the drying process; or it combines with collagen to change its surface properties, hindering the penetration of the acid etching additive. When silica is used in combination with xanthan gum, the shear bonding strength also decreases to a certain extent compared to using silica alone.
[0047] (4) The results of each treatment in Example 3 illustrate the importance of choosing the type of cosolvent. When the cosolvent is a single component, the effect of polyethylene glycol is more obvious. This is because polyethylene glycol has less residue and low hygroscopicity, which makes it easier for the dentin surface to be moderately moistened after acid etching, and the collagen fibers remain in a porous and open state. The strong hydrophilicity of glycerol allows it to penetrate into the collagen fiber network, and the etching additive can penetrate the space. Due to its strong hygroscopicity, glycerol makes the excessive moist state aggravate the collapse of collagen fibers, and the demineralized collagen fiber network remaining on the dentin surface will also form a hydration layer, which hinders the penetration of the etching additive. When polyethylene glycol and glycerol are used in combination, the shear bond strength decreases compared to using polyethylene glycol alone.
[0048] (5) Example 4 uses 4-META, which has stronger amphiphilicity, instead of the acid-etching additive of the present invention, but the shear bonding strength is significantly lower than that of the present invention. This is because the strong amphiphilicity makes it easier for 4-META to penetrate into the structure of collagen fibers. This deep penetration causes 4-META to combine with the polar groups of the collagen peptide chains, resulting in uneven swelling force inside the fibers, which in turn destroys the cross-linking stability between the fibers. The acid anhydride groups of 4-META excessively combine with the hydroxyl groups of collagen, weakening the intramolecular hydrogen bond network of the collagen fibers themselves. In addition, carboxylic anhydride is easily hydrolyzed in a humid environment. After generating carboxylic acid, the interfacial acidity increases, which accelerates the hydrolysis of the resin and leads to a decrease in long-term bonding strength.
[0049] (6) Example 5 uses purely hydrophilic, non-polymerizable glycerol instead of the acid etching additive of the present invention, and the shear bonding strength is also lower than that of the present invention. This is because, although the hydroxyl groups of glycerol can form hydrogen bonds with collagen, its molecular configuration (flexible chain) causes disordered hydrogen bond arrangement, which cannot form a stable support; the hygroscopicity and low volatility of glycerol cause excessive wetting of the dentin surface after acid etching, swelling of collagen fibers, and residual water exacerbating fiber collapse under the action of capillary force; and the small molecular characteristics of glycerol make it easy to seep out of the collagen gap. Glycerol does not contain polymerizable double bonds and cannot form chemical bonds with subsequent adhesive materials and resins through free radical reactions, resulting in poor compatibility.
[0050] (7) The comparative example did not contain an acid-etching additive. Compared with treatment 1-1, the shear bond strength of the comparative example was significantly reduced at the same drying degree. This is because the loss of water during the drying process caused the collagen fiber network to collapse, which affected the shear bond strength. It also shows that the acid-etching additive of the present invention has a significant effect on improving the shear bond strength of the adhesive material on the dentin surface.
[0051] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various variations or modifications within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. An acid etching additive, characterized in that: The acid etching additive can penetrate into the dentin collagen fiber network during the acid etching process, be miscible with the water in the dentin collagen fiber network, and be retained in the dentin collagen fiber network during the drying process to maintain the upright and fluffy structure of the collagen fibers.
2. The acid etching additive according to claim 1, wherein: The present invention comprises at least one of hydroxyethyl methacrylate, N-acryloylmorpholine and 2-hydroxyethyl acrylate.
3. A phosphoric acid etching agent, characterized in that Calculated by weight percentage, the composition comprises: 34-38% phosphoric acid, 25-43% purified water and 1-5% of the acid etching additive according to claim 1 or 2.
4. The phosphoric acid etchant according to claim 3, wherein: Also included is 3-10% of a thickener.
5. The phosphoric acid etchant according to claim 4, wherein: The thickener includes at least one of silicon dioxide and xanthan gum.
6. The phosphoric acid etchant according to any one of claims 3 to 5, characterized in that: Also includes 0.01-0.1% of a color developer.
7. The phosphoric acid etchant according to claim 6, wherein: Also included is 15-30% of a co-solvent.
8. The phosphoric acid etchant according to claim 7, wherein: The cosolvent includes at least one of polyethylene glycol and glycerol.
9. A method for preparing the phosphoric acid etchant according to any one of claims 3 to 8, characterized in that: Combine all the ingredients and stir well.
10. Use of the phosphoric acid etching agent according to any one of claims 5 to 8 in dentin bonding pretreatment, characterized in that: S1. applying the phosphoric acid etchant to the dentin surface for etching; S2. Rinse off the phosphoric acid etchant on the dentin surface and then blow dry. S3. Repair with adhesives and resins.
Citation Information
Patent Citations
Phosphoric acid etching agent and preparation method thereof
CN111467248A